Maxillary molar root and canal morphology of Neolithic and modern Chinese. (November 2021) - Ren, H.Y.; Kum, K.Y.; Zhao, Y.S.; Yoo, Y.J.; Jeong, J.S.; Perinpanayagam, Hiran; Wang, X.Y.; Li, G.J.; Wang, F.; Fang, H.; Gu, Y.
Abstract: Objective: This study aimed to characterize Neolithic human maxillary molars from archeological remains at the Jiaojia site, Shandong, China, and compare their ultrastructural features with sex and age-matched modern locals. Design: Maxillary first (n = 86) and second (n = 80) molars in 5000-year-old individuals (n = 50) from the Jiaojia site were scanned by cone-beam computed tomography (CBCT). Sex and age-matched control groups were assigned from oral surgical patients at Shandong University. Images were analyzed for crown size, root length, root morphology, canal inter-orifice distances, mesiobuccal canal morphology, and second mesiobuccal (MB2) canal prevalence and location. Neolithic and modern values were compared statistically using Chi-squared and Mann-Whitney test at p  < .05. Results: Crown and root size were smaller, and canal inter-orifice distances were shorter in Neolithic maxillary molars than their modern counterparts. For mesiobuccal roots, Weine's Type I single canals were the most prevalent in Neolithic and modern first and second molars. MB2 canal prevalence were not significantly different ( p  > .05) in Neolithic (53.3%) or modern (60.5%) first molars, and Neolithic (11.3%) or modern (21.3%) second molars. But, MB2 prevalence was significantly higher for modern than ancient male first ( p  = .032) and second ( p  = .005) molars. Additionally, MB2 were located more mesially and closer to MB1 in Neolithic than modern molars. Conclusions: Maxillary molar root and canal morphology of ancient 5000-year-old remains at the Jiaojia site resemble that of local patients. A trend towards larger tooth size, and more dispersed MB2 canals over this short evolutionary period warrants additional investigation. Highlights: Crown and root size were smaller in Neolithic maxillary molars than modern clinical cases. Second mesiobuccal canals were less prevalent in Neolithic maxillary molars than their counterparts, especially in males. Canal orifice locations were less dispersed in Neolithic than modern maxillary molars.